Physical simulation and numerical simulation of flash butt welding for innovative dual phase steel DP590: a comparative study - Song, Jingwen; Zhu, Lisong; Wang, Jun; Lu, Yao; Ma, Cheng; Han, Jian; Jiang, Zhengyi (MDPI, 2023)
In this study, the microstructure and performance of newly designed dual-phase steel (DP590) after joining by flash butt welding (FBW) for vehicle wheel rims was analysed and compared by two simulations, i.e., physical simulation and numerical simulation, due to the high acceptance of these two methodologies. Physical simulation is regarded as a thermal–mechanical solution conducted by the Gleeble 3500 simulator and which can distribute the heat-affected zone (HAZ) of the obtained weld joint into four typical HAZs. These are coarse-grained HAZ, fine-grained HAZ, inter-critical HAZ and sub-critical HAZ. A combination of ferrite and tempered martensite leads to the softening behaviour at the sub-critical HAZ of DP590, which is verified to be the weakest area, and influences the final performance due to ~9% reduction of hardness and tensile strength. The numerical simulation, relying on finite element method (FEM) analysis, can distinguish the temperature distribution, which helps us to understand the relationship between the temperature distribution and real microstructure/performance. Based on this study, the combination of physical and numerical simulations can be used to optimise the flash butt welding parameters (flash and butt processes) from the points of temperature distribution (varied areas), microstructure and performance, which are guidelines for the investigation of flash butt welding for innovative materials.
Keywords: flash butt welding; dual-phase steel; thermal-mechanical simulation; numerical simulation; heat affected zone; oftening behaviour